Comparison of the accuracy of maxillary position between conventional model surgery and virtual surgical planning. Issue 2 (February 2018) - Ritto, F.G.; Schmitt, A.R.M.; Pimentel, T.; Canellas, J.V.; Medeiros, P.J.
Abstract: The aim of this study was to determine whether virtual surgical planning (VSP) is an accurate method for positioning the maxilla when compared to conventional articulator model surgery (CMS), through the superimposition of computed tomography (CT) images. This retrospective study included the records of 30 adult patients submitted to bimaxillary orthognathic surgery. Two groups were created according to the treatment planning performed: CMS and VSP. The treatment planning protocol was the same for all patients. Pre- and postoperative CT images were superimposed and the linear distances between upper jaw reference points were measured. Measurements were then compared to the treatment planning, and the difference in accuracy between CMS and VSP was determined using the t -test for independent samples. The success criterion adopted was a mean linear difference of <2 mm. The mean linear difference between planned and obtained movements for CMS was 1.27 ± 1.05 mm, and for VSP was 1.20 ± 1.08 mm. With CMS, 80% of overlapping reference points had a difference of <2 mm, while for VSP this value was 83.6%. There was no statistically significant difference between the two techniques regarding accuracy ( P > 0.05).